A novel scaffold-free mesenchymal stem cell-derived tissue engineered construct for articular cartilage restoration - From basic to clinic - Kazunori Shimomura; Wataru Ando; David A. Hart; Norimasa Nakamura (Regenerative Therapy)
Treatments for articular cartilage injuries are still challenging, due in part to its avascular and aneural surroundings. Since the first report of autologous chondrocyte implantation, cell-based therapies have been extensively studied with a variety of cell sources, including chondrocytes and mesenchymal stem/stromal cells (MSCs). Recently, MSC-based therapy has received considerable research attention because of the relative ease in handling for tissue harvest, and subsequent cell expansion and differentiation. Using such cells, we have originally developed a 3-dimensional scaffold-free tissue-engineered construct (TEC) through simple-cell culture methods and demonstrated its feasibility for cartilage repair and regeneration in the first-in-human clinical trial. This review summarizes our novel scaffold-free approaches to use MSC for the restoration of damaged articular cartilage, documenting the progression from basic to clinical studies.